How semantic content of stimuli works on episodic memory processes in negative schizophrenia: Evidence from picture recognition - Merlet, L.B.; Blanchet, A.; Lockman, H.; Kostova, M. (Elsevier, 2016)
Introduction Even though episodic memory is impaired in schizophrenia, semantic processing strategies can improve patients’ performance. However, it is less clear if negative schizophrenia patients can benefit from semantic strategies, and if both familiarity and recollection processes can be enhanced in patients with schizophrenia. Objective The aim of this study was to investigate the possibility for negative schizophrenia patients to enhance their familiarity and/or recollection processes in the presence of concrete images. Method A recognition memory task using concrete versus abstract images as stimuli was designed to assess the performance of schizophrenia patients for single item recognition and the recollection of spatial context, allowing us to calculate the estimates of familiarity and recollection processes. Thirty-six patients with schizophrenia and 18 healthy individuals participated to the study. Schizophrenia patients were divided into two groups according to their scores on the negative scale of the Positive and Negative Syndrome Scale for Schizophrenia (PANSS). Results Results showed that, while healthy participants enhanced their recollection estimates in the presence of concrete images, both schizophrenia groups could enhance their familiarity estimates. Conclusion Semantic strategies are helpful to promote successful familiarity process in schizophrenia patients, independently from clinical dimension of negativity. However, recollection process seems not to respond to such strategies.